2021
DOI: 10.1097/shk.0000000000001862
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl Ethyl Starch (HES) Preserves Intrarenal Microcirculatory Perfusion Shown by Contrast-Enhanced Ultrasound (Ceus), and Renal Function in a Severe Hemodilution Model in Pigs

Abstract: Acute normovolemic hemodilution (ANH) is associated with low oxygen carrying capacity of blood and purposed to cause renal injury in perioperative setting. It is best accomplished in a perioperative setting by a colloid such as hydroxyl ethyl starch (HES) due its capacity to fill the vascular compartment and maintain colloidal pressure. However, alterations of intra renal microvascular perfusion, flow and its effects on renal function and damage during ANH has not been sufficiently clarified. Based on the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(38 reference statements)
2
0
1
Order By: Relevance
“…The injury is followed by a whole blood transfusion. This is consistent with current resuscitation practices and avoids the hemodilution that impairs hemostasis and does not play a causal role in MBF derangement (32). The model produces a loss of coherence between macrohemodynamics and microhemodynamics, which is consistent with clinical observations and can be difficult to capture with other methods of measuring MBF (33).…”
Section: Discussionsupporting
confidence: 85%
“…The injury is followed by a whole blood transfusion. This is consistent with current resuscitation practices and avoids the hemodilution that impairs hemostasis and does not play a causal role in MBF derangement (32). The model produces a loss of coherence between macrohemodynamics and microhemodynamics, which is consistent with clinical observations and can be difficult to capture with other methods of measuring MBF (33).…”
Section: Discussionsupporting
confidence: 85%
“…In this study, we showed that aggressive fluid resuscitation could improve the systemic hemodynamic parameters such as MAP, CVP, and cardiac output following non-traumatic hemorrhagic shock, despite low systemic vascular resistance (SVR) and consistent tissue hypoxia shown by plasma lactate and serum creatinine levels. Similar to our previous study in stepwise hemodilution in pigs [26], it is shown that the correction of systemic hemodynamic variables was not accompanied with the improvement of renal cortical perfusion, intra-renal blood volume, renal damage, and systemic microcirculation following 1 h of fluid resuscitation. Lastly, we suggest that, regardless of fluid type, fluids need to be administered to patients with caution, and the measurement of renal injury biomarkers and microcirculatory assessments can be used for guiding the optimization of therapies.…”
Section: Limitationssupporting
confidence: 87%
“…Interestingly, despite RVR was normalized probably due to renal autoregulation, SVR was still depleted throughout the experiment because of the low blood viscosity. In our previous study, we demonstrated that high RBC velocity could persist during hemodilution with HES, which resulted in renal damage without the association of hyperlactatemia despite sustained or, in some part, improved systemic and renal hemodynamics [26]. However, in the present study, we found that the sublingual RBC velocity was not influenced after normalization of systemic hemodynamics by crystalloid resuscitation, but there were less capillaries than…”
Section: Discussioncontrasting
confidence: 76%